Desorption of Metals from Aquifer Soils During Infiltration of Low Ionic Strength Water by pH Effect - Huang, Xianhuai; Xue, Junjie; Li, Qilin; Tang, Yuchao (Asian Journal of Chemistry, 2014)
Primary and trace metals from S400 samples are higher than that from S700 because the size of S400 is smaller than one of S700. The effects of solution chemistry, i.e., ionic strength and pH, on metal immobilization were evaluated via batch desorption equilibrium experiments for aquifer soils during infiltration of low ionic strength water. For S400 and S700, cumulative desorption amount of Ca is, respectively 2050 and 1900 mg/kg-soil with 12 times extraction at 58 mg/L of TDS water at pH = 4. It was found that desorption of Ca, Mg and Ba decreases with increasing pH. For S400 and S700, cumulative desorption amount of As is 0.9 mg/kg-soil with 15 times extraction at 58 mg/L of TDS water at pH = 9. On the contrary, desorption of As was found to increase slightly with increasing solution pH, although the effect of pH is not as great as that for the other metals. This effect was offset by the less dissolution of CaCO3 at higher pH, which reduced release of carbonate associated arsenic.